A NOVEL CLINICAL LANDMARK FOR JACOBSON’S NERVE: RAO’S POINTER - Dr. Santhanakrishnan Kaliavaradan; Dr. Poornima S. Bhat; Dr. Satyananda Rao Sutrave; Dr. Nisha M.; Dr. Rahul Panwar; Dr. Shwetank Manjul (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: The tympanic branch of Glossopharyngeal nerve, also called as Jacobson nerve, is a useful landmark in identifying the anterior and posterior parts of the basal segment of the scala tympani of particular relevance in cochlear implantation. It is also sectioned in cases of Frey’s syndrome. This study was conducted to assess the usefulness of handle of malleus (Rao’ pointer)  as a novel landmark for the identification of Jacobson’s nerve over the promontory.Methods: This prospective, cross- sectional observational study included the patients in the age group of 12- 70 years, with Chronic Otitis Media, inactive mucosal type with large to subtotal central perforation. Findings of were noted using otoscope and endoscope with special attention to Jacobson’s nerve and its relationship with the Handle of malleus. The position of the nerve was marked, by plotting the otoendoscopy image to an imaginary clock position by considering the lateral process of malleus at 12’ O clock position. Statistical analysis was performed usingResults: Out of the total 162 tympanic membrane perforations examined, in 110 patients with COM, the following findings were noted. In 11(6.69%) ears, Jacobson nerve was not visible on the promontory. In 143(88.27%) ears, Jacobson’s nerve was visible on the promontory, parallel to the handle of malleus, along the imaginary 6’0 clock position (Rao’s Pointer).  In rest 8(4.94%) cases, it was slightly posterior, between the 6 o’ clock -  7 o’ clock on left side and  6 o’ clock to 5 o’ clock on right side, respectively.Conclusion: Rao’s pointer can be used as a valuable clinical landmark to identify this nerve in majority of the patients in various ear surgeries and also in undergraduate and postgraduate training. Further studies with intraoperative correlations and exact distance measurements are recommended.